Observation and modelling of local wind circulation in the complex topography of Svalbard archipelago - Chládová, Z. (Zuzana); Láska, K.; Hošek, J. (Jiří) (2016)
The atmospheric boundary layer processes over Svalbard fjords are strongly influenced by complex topography and sea ice occurence. In this study we point at foehn winds and low level jets in surrounding of Petuniabukta in central part of Spitsbergen. We used the Weather Research and Forecasting mesoscale model. The low level jets and wind have been successfilly simulated by the model.